Social inequalities in road traffic deaths at age 16–20 years among all 611 654 Norwegians born between 1967 and 1976: a multilevel analysis. Issue 1 (23rd May 2011) - Kristensen, Petter; Kristiansen, Thomas; Rehn, Marius; Gravseth, Hans Magne; Bjerkedal, Tor
Abstract : Background: Road traffic injury is a major cause of death among youths. Aims: To estimate mortality differences in family socioeconomic position (SEP) and municipal disadvantage level. Methods: Data on all Norwegians born in 1967–76, gathered from national registries, were linked by a unique national identification number. The 611 654 participants were followed-up for 5 years from age 16 years. Parental education level, father's income level, and proportion of high-income earners in the municipality served as SEP indicators. Associations between SEP and road traffic deaths were analysed by multilevel Poisson regression. Results: Road traffic deaths (n=676, rate 22.2 per 100 000 person-years) constituted a major cause of death, of which 91.9% were motor vehicle occupants. SEP distributions differed according to gender and type of motor vehicle crash (collision, non-collision). There was an inverse relationship between municipal proportions of high-income earners and mortality (population attributable fraction (PAF) 0.43, 95% CI 0.30 to 0.53) in all categories of gender-specific crash types. Family SEP gradients were not found except for male non-collision deaths, where increasing mortality was found in association with decreasing parental education level (PAF 0.94, 95% CI 0.59 to 0.99) and increasing paternal income (PAF 0.25, 95% CI 0.06 to 0.40). Conclusion: The different SEP patterns for road traffic deaths across gender and motor vehicle crash type illustrate that heterogeneity of social inequalities in health can be found even within narrow age bands and for similar causes of death.